استراتيجيات حماية شبابنا من الانعكاسات السلبية للعولمة الثقافية- المخدرات الرقمية أنموذجا- - فرحات, أحمد; غدايفي, هند (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى الحرص على حماية شبابنا إناثا وذكورا من جميع مخاطر العولمة الثقافية ،حيث استغل العقل البشري وللأسف الشديد التقنيات الحديثة والمتمثلة في الشبكة العنكبوتية (الأنترنت) وانتشارها الرهيب وتدفقها العالي للترويج والتسويق لمجموعة من الانحرافات الدينية والثقافية والأخلاقية والأسرية والاقتصادية والتربوية والسياسية حتى أصبح الشباب رهينة الإدمان عليها، لأن هذه التقنية جعلت الشاب يعيش في عالم بدون حدود وتدفق بغير موانع، ومن هذه الانحرافات المخدرات الرقمية والتي بدأت تنتشر في الوطن العربي لدى فئة الشباب وهي عبارة عن ملفات صوتية وتكون أحيانا مرفوقة بصور بصرية وأشكال وألوان تتحرك وتتغير لتخادع الدماغ عن طريق الأمواج الصوتية الموجهة وبتردد مختلف للأذنين....فهي تؤثر على ثقافة الشاب وإدراكه ولغته وسلوكه وانتمائه ومن هذا المنطلق أصبح لزاما التدخل وتوحيد الجهود لحماية شبابنا من هذه العاصفة التي عصفت بشباب العديد من الدول الغربية وبعض الدول العربية والتصدي لها بأفكارنا ونرفع من مستوى وعي الشباب الجزائري انطلاقا من المؤسسات التربوية بالتنسيق مع مختلف المؤسسات الأمنية لوضع استراتيجية للحد من انتشار هذه الجريمة الالكترونية. The study aims to protect our young men and women from all the dangers of cultural globalization. Unfortunately, the human mind exploited the modern technologies of the Internet, its terrible spread and its high flow to promote and market a range of religious, cultural, moral, family, economic, educational and political deviations, Hostage of addiction. Because this technique made the young man lives in a world without limits and flow without impediments. These digital drug deviations, which began to spread in the Arab world in the youth, are audio files and sometimes accompanied by visual images, shapes and colors that move and change to deceive the brain through wave waves Different to the ears. It affects the culture of the young man and his awareness and language and behavior and affiliation and from this point it became necessary to intervene and unite efforts to protect our youth from this storm, which afflicted the youth of many Western countries and some Arab countries and address them with our ideas and raise the level of awareness of young people From the educational institutions in coordination with various security institutions to develop a strategy to reduce the spread of this electronic crime.
Strategies to protect our youth from the negative repercussions of cultural globalization - digital drugs as a model -
مقال
Keywords: العولمة الثقافية، المخدرات الرقمية، الشباب الجزائري، استراتيجية; Cultural globalization, digital drugs, Algerian youth, strategy